Carotid intima media thickness is independently associated with urinary sodium excretion in patients with chronic kidney disease. (14th September 2015) - Ustundag, Sedat; Yilmaz, Gulay; Sevinc, Can; Akpinar, Seval; Temizoz, Osman; Sut, Necdet; Ustundag, Ayten
Abstract: Atherosclerosis-induced premature vascular diseases are the leading cause of mortality among patients with chronic kidney disease (CKD). The pathogenetic mechanism of atherosclerosis in patients with CKD has not been fully explained. Experimental studies have demonstrated that high dietary sodium intake not only increases circulatory volume and blood pressure, but also facilitates development of atherosclerosis by reducing production-bioavailability of nitric oxide due to oxidative stress and accordingly by enhancing endothelial and arterial stiffness. In this study, we investigated the relationship between sodium consumption and carotid artery intima-media thickness, which is the indicator of atherosclerosis, by determining daily urinary sodium excretion, which is a reliable indicator of sodium consumption, in our patient group. Our patient group included 193 patients with stage 2–4 non-diabetic CKD and without a history of atherosclerotic disease. We determined that 77% of our patients have been consuming more than 2 g of sodium per day, which is the upper limit of sodium consumption recommended for patients with CKD. We determined a positive linear correlation between carotid artery intima-media thickness and patient age ( p < 0.001), C-reactive protein ( p < 0.001), urinary sodium excretion ( p < 0.001), body mass index ( p = 0.002), systolic blood pressure ( p = 0.002), hemoglobin ( p = 0.030), triglycerides ( p = 0.043), and diastolic blood pressure ( p = 0.049). We also found a negative linear correlation between carotid artery intima-media thickness and glomerular filtration rate ( p = 0.008). We found that urinary sodium excretion is the determinant of intima-media thickness even if all factors associated with intima-media thickness are adjusted, and that intima-media thickness increases by 0.031 (0.004–0.059) mm per 2 g increase in daily sodium excretion, independent from overall factors ( p = 0.025). Our results reveal a relation between urinary sodium excretion and carotid artery intima-media thickness and suggest that excessive sodium consumption predisposes development of atherosclerosis in patients with CKD.